America's digital army : games at work and war - Allen, Robertson (Anthropology of contemporary North America., 2017)
"An ethnographic study based on scholar Robertson Allen's years of behind-the-scenes ethnographic fieldwork within the work environments of the video game developers, military strategists, enlisted soldiers, and defense contractors who produced the official U.S. Army video game, "America's Army.""--